Resilience mediates the effect of the COVID-19 pandemic on mental health in a sample of adults in Panama - Oviedo, Diana C.; Tratner, Adam E.; Pinzón, María Sofía; Rodríguez-Araña, Sofía; Pauli-Quirós, Elianne; Chavarría, Carlos; Rodríguez, Camilo Posada; Britton, Gabrielle B. (Frontiers in Psychology, 2023)
Background The COVID-19 pandemic was characterized by global increases in depression, anxiety, and stress symptoms. Previous studies have shown that resilience mitigates these symptoms, however there is limited research exploring the link between resilience and mental illness during the COVID-19 pandemic in Central America. Objective To examine the role of resilience as it relates to the perceived effect of the pandemic on mental health symptoms. Methods A sample of 480 adults in Panama were recruited from March to May 2021 to complete an online survey. The online survey consisted of sociodemographic questions and scale measures assessing depression, anxiety and stress symptoms, resilience, and social support. Results Results indicated that resilience mediated the relationship between the perceived effect of the COVID-19 pandemic and mental health symptoms; participants who felt more personally affected by the pandemic reported more depression, anxiety, and stress symptoms via decreased resilience. Further analyses revealed that resilience was moderated by sex and social support, showing that the indirect effect of resilience was greater for women and individuals who perceived low social support. Discussion These findings contribute to a growing body of research documenting the adverse effects of the COVID-19 pandemic on mental health and reveal potential mechanisms through which pandemic-related distress decreases resilience, thereby increasing symptoms of mental illness.